Reducing Radicalism Transformation: Reviewing the Role of Government through the Programs of Deradicalization - Hergianasari, Putri; Wijanarka, Tunjung; Akarapisan, Kannaporn Pam (JSW (Jurnal Sosiologi Walisongo), 2024)
Initiatives to promote democracy in Indonesia continue to face several difficulties and hurdles. One of the major concerns is the emergence of radical ideas arising and hiding under the guise of democracy. Due to globalization, radicalism has evolved rapidly and taken on new forms. Considerable efforts are needed to maintain democratization in Indonesia, according to Pancasila, the foundational philosophical theory. This qualitative research uses descriptive analysis and data-gathering methods based on a review of current literature, such as news, journal articles, and books. The findings show that radical ideology in Indonesia has evolved and penetrated government bodies and people’s social lives. Terrorist-affiliated radical organizations, many of which have been disbanded, morphed into different forms to adapt to the community’s social lives. The transformation of radicalism in Indonesia necessitates a concerted effort on the part of the government as a state entity capable of deradicalizing education and preventing radical ideology.